1998
DOI: 10.1074/jbc.273.30.19060
|View full text |Cite
|
Sign up to set email alerts
|

Acylation of Naturally Occurring and Synthetic 1-Deoxysphinganines by Ceramide Synthase

Abstract: Fumonisin B 1 (FB 1 ) is the predominant member of a family of mycotoxins produced by Fusarium moniliforme (Sheldon) and related fungi. Certain foods also contain the aminopentol backbone (AP 1 ) that is formed upon base hydrolysis of the ester-linked tricarballylic acids of FB 1 . Both FB 1 and, to a lesser extent, AP 1 inhibit ceramide synthase due to structural similarities between fumonisins (as 1-deoxy-analogs of sphinganine) and sphingoid bases. To explore these structure-function relationships further, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 143 publications
(73 citation statements)
references
References 35 publications
3
69
0
1
Order By: Relevance
“…The rapid and extensive acylation of 1-deoxySa is not surprising since studies of the structural requirements of sphingoid bases as substrates and inhibitors of CerS had previously shown that this compound was acylated (37). In LY-B-LCB1 cells FB 1 caused a much larger increase in 1-deoxySa (40 pmol/mg protein) than can be accounted for solely by the levels of 1-deoxyDHCer in the untreated cells.…”
Section: Discussionmentioning
confidence: 91%
“…The rapid and extensive acylation of 1-deoxySa is not surprising since studies of the structural requirements of sphingoid bases as substrates and inhibitors of CerS had previously shown that this compound was acylated (37). In LY-B-LCB1 cells FB 1 caused a much larger increase in 1-deoxySa (40 pmol/mg protein) than can be accounted for solely by the levels of 1-deoxyDHCer in the untreated cells.…”
Section: Discussionmentioning
confidence: 91%
“…1A). Nevertheless, the DSBs serve as a substrate for ceramide synthase as shown previously by testing the effect of several synthetic sphingoid base analogs (23). The DSBs are N-acylated and also desaturated by ceramide desaturase (DES), which results in the formation of deoxy-ceramide and deoxymethyl-ceramide.…”
Section: Hsan1 Mutations Induce a Shift In Spt Substratementioning
confidence: 99%
“…Structure-function investigations suggest that the aminoalkyl backbone competes with the sphingoid base binding site of (dihydro)ceramide synthase, and the anionic tricarballylic side chains interfere with utilization of the co-substrate fatty acylCoA; thus, compounds with the aminopentol backbone alone (AP 1 in Fig. 2) are both substrates and inhibitors (41).…”
Section: De Novo Sphingolipid Biosynthesismentioning
confidence: 99%